Journalistic discourse and immigration. Recommendations for an approach in human rights - Rodríguez Arrieta, José Daniel (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2023)
This paper aims to provide a series of practical recommendations linked with the respect for human rights for journalistic work then they address the phenomenon of immigration. For this task, theoretical and conceptual contributions about the discourse analysis, theory of framing, and human rights theory are collected. Based on this conceptual framework this paper shows the importance of journalistic approaches when they present news related to the phenomenon of immigration.